Epigenetic protein families: a new frontier for drug discovery. - Arrowsmith, C; Bountra, C; Fish, P; Lee, K; Schapira, M (2012)
Epigenetic regulation of gene expression is a dynamic and reversible process that establishes normal cellular phenotypes but also contributes to human diseases. At the molecular level, epigenetic regulation involves hierarchical covalent modification of DNA and the proteins that package DNA, such as histones. Here, we review the key protein families that mediate epigenetic signalling through the acetylation and methylation of histones, including histone deacetylases, protein methyltransferases, lysine demethylases, bromodomain-containing proteins and proteins that bind to methylated histones. These protein families are emerging as druggable classes of enzymes and druggable classes of protein-protein interaction domains. In this article, we discuss the known links with disease, basic molecular mechanisms of action and recent progress in the pharmacological modulation of each class of proteins.